Integrating blockchain into the circular economy: A bibliometric and systematic literature review - Berghout, Oussama; Kedatsa, Mohamed; Ali, Kaddour; Hadadou, Mahfoud (The International tax journal, 2025)
The integration of blockchain (BC) technology into the circular economy (CE) is fast growing, but comprehending the long-term and real implications of such integration needs more extensive research. To address this research gap, we offered an integrated technique that combines bibliometric analysis with systematic literature review (SLR). The bibliometric analysis provided a complete perspective of the issue, demonstrating India's global leadership in this domain. It also identified the most important educational institutions, scientific publications, keywords, and notable researchers in this discipline. The SLR comprised a thorough review of 20 well-chosen scholarly literature. It focused on the contemporary uses of BC in the circular economy. We've identified three primary areas for BC applications: manufacturing, waste management, and supply chains. Despite their great potential, they face a variety of constraints, which may be divided into four categories: administrative challenges, technological and financial impediments, social challenges, privacy concerns, and security issues. The study finds that successful integration of BC into the CE necessitates more research, notably on the technological and economic viability of the integration.